Reaksi Pasar Modal Akibat Pengumuman Kenaikan Harga Bahan Bakar Minyak pada Saham LQ45 Bursa Efek Indonesia - Sari, Kadek Ira Martavitha; Candraningrat, Ica Rika (E-Jurnal Akuntansi; Vol 33 No 12 (2023)DO - 10.24843/EJA.2023.v33.i12.p12, 2023)
The announcement of an increase in fuel prices is an informative event for investors and can influence share prices in the capital market. This research aims to determine the capital market reaction due to the announcement of an increase in fuel prices on September 3 2022. This research was conducted on companies listed on the BEI LQ45 index using a saturated sampling technique. The date for the event is set on Monday, September 5 2022, which is the first trading day after the announcement of the fuel price increase on September 3 2022 taking effect. The event period in this research is 7 trading days. Hypothesis testing in this research uses one sample t-test. The research results show that the announcement of the fuel price increase on September 3 2022 did not create significant abnormal returns around the event, which shows that the market is in an efficient condition in a semi-strong form. Keywords: Abnormal Return; Efficient Market Hypothesis; Fuel Price Increase; Capital Market Reaction; Signaling Theory